THE EFFECT OF ALCOHOLIC EXTRACT Eriobotrya japonica LEAVES ON SOME BACTERIAL GENES AND SOME CHEMICAL AND MICROBIOLOGICAL PROPERTIES OF BEEF - & et al., Alwash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to investigate the effect of using alcoholic extract of yangadnia leaves on some bacterial strain Salmonella typhimiurum, E.coli and staphylococcus aures in 200, 100, 50 and 25 mg/ml concentration using digging method. Minced cow meat 200 mg/ml was mixed with yangdina extract and stored for 0,2,4 day at 4 C and tested for chemical and biological characteristics. The ruselts showed that the best concetration of inhibition was 200mg/ml and the inhibition zone diameters were 26, 19, 15 mm for S. aures, S. typhimiurm and E .coli respectively. In respect to Effect of extract in minced cow the ruselts showed drop in values of, thiobarbituric acid (TBA),total violate nitrogen (TVN), total number account of bactria and count of psycrotrophic bactria and effect on PH values. It can be concluded that yangdina leaves extract has inhibitory effect on bacterial strain and best concetration 200mg/ml. Mixing meat with extract improved the storage life at 4c for 4 day.